Agricultural sector of Kazakhstan's economy: problems and ways to solve them - Sauranbai, S.B.; Baidybekova, S.K.; Abdykulova, D.B.; Arystanbayeva, S.S.; Kitapova, К. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the study is to reflect the real state of the agar industry, to reveal the main problems of development, in particular crop production in the whole country, as well as in the context of regions. To achieve this goal, the following tasks were set: reflection of the role of the agricultural sector of the economy in modern economic conditions; analysis of the main quantitative and qualitative indicators of crop production; identification of the main problems in the agricultural sector and ways to solve them. Methods: During the research, various methods were used in the work: induction and deduction, analysis and synthesis, economic and statistical analysis of economic indicators. Findings: Based on the results of the conducted research, a set of measures for the growth and development of the agricultural sector of the economy has been determined: work to increase the investment attractiveness of the industry, the use of diversification of agricultural acreage as one of the ways to increase crop yields, etc. Conclusions: The application of all measures in a complex will contribute to the growth and development of the agricultural sector of the economy, raising the prestige of rural areas, increasing the level of investment attractiveness, the level and quality of life of the rural population.